- #1

- 15

- 0

## Main Question or Discussion Point

A mathematical operator (Aop) operates on a function (f) to generate a new function (f '):

Aop (f) = f ' (1)

Consider that I subtract a from b to get c:

b-a = c (2)

Can I write this subtraction operation as an operator equation of the form (1) as shown below?

(-a) (b) = c (3)

where (-a) represents the operator "subtract a".

Similarly for +, x and /.

Aop (f) = f ' (1)

Consider that I subtract a from b to get c:

b-a = c (2)

Can I write this subtraction operation as an operator equation of the form (1) as shown below?

(-a) (b) = c (3)

where (-a) represents the operator "subtract a".

Similarly for +, x and /.